Organizational and legal aspects of ensuring infrastructural interaction between business and higher education - Yu. V. Kotelevskaya (Вестник университета)
The legal foundations’ study for ensuring infrastructural interaction between business and higher education is the basis for building a hypothesis about the need to improve the conditions for the effective use of scientific developments, the development of intellectual capital and commercialization, as well as for the practical applicability of research achievements. The article analyzes the legislative basis that forms the basis for the interaction of business and higher education, where it is justified that small and medium-sized businesses should act as entrepreneurial activities. The analysis made it possible to identify shortcomings in the legislation that do not consider the requests of all interested parties (stakeholders). The interrelation of national projects is considered and it is highlighted that at the moment there is a trend in legislation to create conditions for interaction between business and higher education. In addition, a number of arguments are given justifying that in order to achieve economic development considering digital transformations of the economy, it is necessary to create conditions for ensuring infrastructural interaction between business and higher education, where small and medium-sized businesses act as entrepreneurship with the active participation of authorities.